Rancang Bangun Sistem Throttle Brushless DC Motor pada Kursi Roda Elektrik - Natanael, Ferdinand; Arthaya, Bagus Made; Wahab, Faisal (ELECTRON Jurnal Ilmiah Teknik Elektro, 2025)
An electric wheelchair is a mobility aid designed to support the activities of individuals with physical disabilities, particularly those who have difficulty moving independently. This device consists of several main components, including a mechanical frame with four wheels two drive wheels powered by electric motors and two caster wheels at the front as well as a control system in the form of a joystick, a battery as the power source, and a seat designed for user comfort. With the advancement of technology, it is essential to integrate more efficient and accurate control systems into electric wheelchairs. This study aims to design and develop a throttle and tachometer system based on a Hall-effect sensor for electric wheelchairs to enhance movement control and accuracy. The system allows users to operate the wheelchair to move forward, turn right, and turn left using only the joystick. The methodology includes modifying a conventional wheelchair frame, integrating a BLDC motor, designing the throttle system, and implementing a Hall-effect sensor for real-time wheel rotation speed measurement. The results show that the Hall-effect sensor-based tachometer system demonstrates a high level of accuracy, with a measurement error of only 0.32% compared to standard measuring instruments. The BLDC motor used in the system is capable of reaching a maximum rotational speed of 450 RPM. These findings prove that the developed system improves the performance and reliability of electric wheelchairs while providing better comfort and independence for users.